Green Synthesis, Characterization, Antibacterial Activity of Heterocyclic Compounds from Chalcone on Basis of in vitro and Quantum Chemistry Calculation - Ahamd Khan, Salman; Mohamed Asiri, Abdulllah; A.K. Elroby, Shabaan (Asian Journal of Chemistry, 2014)
Heterocyclic compounds such as pyrazolines and pyrimidines were synthesized by the reaction of thiosemicarbazide/phenyl hydrazine/hydrazine hydrate/thiourea/guanidine hydrochloride with 3(4-dimethylamino-phenyl)-1-(2,5-dimethyl-thiophen-3-yl)-propenone under microwave irradiation. The chalcone was derived from the reaction of 3-acetyl-2,5-dimethylthiophene with p-dimethylamino benzaldehyde. Pyrazoline and pyrimidine derivatives were obtained in good to excellent yields. All the new compounds were characterized by IR, 1H NMR, 13C NMR, MS and elemental analyses. The antibacterial activity of these compounds were tested in vitro by the disk diffusion assay against two Gram-positive and two Gram-negative bacteria. The results showed that one of the pyrazoline derivatives is better at inhibiting the growth as compared to chloramphenicol against both types of the bacteria (Gram-positive and Gram-negative). Furthermore, Quantum chemistry calculations of the electronic structure of the studied molecules using DFT/B3LYP/6-311++G** level of theory have confirmed the results. Charge distribution and frontier molecular orbitals of the studied molecules were also investigated.